4D printing with robust thermoplastic polyurethane hydrogel-elastomer trilayers - Anna B. Baker; Simon R.G. Bates; Thomas M. Llewellyn-Jones; Laurie P.B. Valori; Michael P.M. Dicker; Richard S. Trask (Materials & Design, 2019)
Here we present a new 4D printing technique capable of producing a diverse range of trilayer constructs using commercial low-cost desktop 3D printers. This unique methodology permits the viable construction of dynamically robust and complex origami architectures for a new generation of active structures. The resulting creations transform from flat 2D parts to 3D structures through submersion in water and return to their original configuration through dehydration. This technique uses commercially available materials and printers to enable a 4D printing method that is more accessible and affordable than previous examples of hydration triggered 4D printing. This method yields a controlled and predictable actuation route and final shape, enabling it to be used for both simple and complex origami inspired designs, such as the tessellated waterbomb origami pattern, a design that has not previously been realised with 4D printing. These new designs demonstrate how the integration of multiple trilayers into a single 3D print enables through-thickness control of actuation and resulting formation of active structures with complexity beyond what has previously been achieved with 4D printing. Keywords: 4D printing, Hydrogels, Thermoplastic polyurethane, Trilayers, Origami, Active structures